Cost Analysis of Brachial Plexus Injuries: Variability of Compensation by Insurance Companies before and after Surgery - Felici, N.; Zaami, S.; Ciancolini, G.; Marinelli, E.; Tagliente, D.; Cannatà, C. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2014)
Traumatic paralysis of the brachial plexus is an extremely disabling pathology. The type of trauma most frequently suffered by this group of patients is due to motorcycle injuries. It therefore affects a population of young patients. In the majority of cases, these patients receive compensation for permanent damage from insurance companies. Surgery of the brachial plexus enables various forms of functional recovery, depending on the number of roots of the brachial plexus involved in the injury. The aim of this study is to compare the functional deficit and the extent of the related compensation before and after surgical intervention, and to evaluate the saving in economic terms (understood as the cost of compensation paid by insurance companies) obtainable through surgical intervention. The authors analysed the functional recovery obtained through surgery in 134 patients divided into 4 groups on the basis of the number of injured roots. The levels of compensation payable to the patient before surgical intervention, and 3 years after, were then compared. The results showed that the saving obtainable through surgical treatment of brachial plexus injuries may exceed 65% of the economic value of the compensation that would have been attributable to the same patients if they had not undergone surgical treatment.
Keywords: plexus surgery in adults; brachial plexus injury; cost analysis